Abusive supervision, high-performance work systems, and subordinate silence. Issue 8 (2nd January 2020) - Xu, Qin; Zhao, Yixuan; Xi, Meng; Li, Fangjun
Abstract : Purpose: The purpose of this paper is to test a mediated moderation model of the joint influence of abusive supervision, high-performance work systems (HPWSs) and organizational commitment and intention to leave on employee silence. Design/methodology/approach: Data were collected from 456 employees and 78 human resource managers in 78 Chinese organizations. Findings: The results revealed that abusive supervision led to subordinate silence, and HPWSs intensified this effect. In addition, such moderating effect of HPWSs was accounted for by employees' organizational commitment and intention to leave. Research limitations/implications: To reduce the occurrence of employee silence, organizations should not only monitor and restrain abusive supervisory actions, but also be aware of subordinates' work attitudes driven by organizational HPWSs. Originality/value: This is the first study which demonstrates that HPWSs can foster employees' organizational commitment and hinder their intention to leave and consequently strengthen the relation between abusive supervision and employee silence.